Dari Pulpit ke Platform: Kerangka Strategis Integrasi Teologi Digital dalam Ibadah Kristen - Sherly Mudak; Ferdinan Samuel Manafe; Sumarno (STT Bala Keselamatan Palu, 2026)
Digital transformation has shifted Christian worship practices from physical spaces to digital platforms, presenting both opportunities and challenges for the church in carrying out its mission and maintaining theological integrity. This study aims to analyze the missiological and ethical implications of digital theology in Christian worship and to formulate strategies for integrating technology that remain grounded in the principles of Christian theology. The study employs a qualitative method using a literature review approach through a critical analysis of books, scholarly articles, and academic documents discussing digital theology, missiology, Christian ethics, and digital transformation in church ministry. The research findings indicate that digital theology not only expands the church’s mission field through the digital mission field but also presents challenges such as the commercialization of ministry, the protection of congregational data, community fragmentation, and a shift in the orientation of worship due to the dominance of digital platform logic. The research findings emphasize that technology must be understood as a supportive tool for ministry, one that complements, rather than replaces, the essence of the church as a community of faith centered on the Word, the work of the Holy Spirit, and the fellowship of believers. This study proposes four strategies for integrating digital theology: strengthening digital literacy among church leaders; developing hybrid worship models; crafting digital liturgies with theological integrity; and developing a digital ethics framework that encompasses data governance, ministry evaluation, and oversight of commercialization. These strategies are expected to serve as a conceptual framework for the church in developing digital ministries that are contextual, responsible, and faithful to Christ’s mission. Abstrak: Transformasi digital telah mengubah praktik ibadah Kristen dari ruang fisik menuju platform digital, sehingga menghadirkan peluang sekaligus tantangan bagi gereja dalam melaksanakan misi dan mempertahankan integritas teologis. Penelitian ini bertujuan menganalisis implikasi misiologis dan etis teologi digital dalam ibadah Kristen serta merumuskan strategi integrasi teknologi yang tetap berlandaskan prinsip-prinsip teologi Kristen. Penelitian menggunakan metode kualitatif dengan pendekatan studi literatur melalui analisis kritis terhadap buku, artikel ilmiah, dan dokumen akademik yang membahas teologi digital, misiologi, etika Kristen, serta transformasi digital dalam pelayanan gereja. Hasil penelitian menunjukkan bahwa teologi digital tidak hanya memperluas ruang misi gereja melalui digital mission field, tetapi juga memunculkan tantangan berupa komersialisasi pelayanan, perlindungan data jemaat, fragmentasi komunitas, serta pergeseran orientasi ibadah akibat dominasi logika platform digital. Temuan penelitian menegaskan bahwa teknologi harus dipahami sebagai instrumen pelayanan yang mendukung, bukan menggantikan, hakikat gereja sebagai komunitas iman yang berpusat pada Firman, karya Roh Kudus, dan persekutuan umat. Penelitian ini menawarkan empat strategi integrasi teologi digital, yaitu penguatan literasi digital bagi pemimpin gereja, pengembangan model ibadah hybrid, penyusunan liturgi digital yang berintegritas teologis, serta pengembangan kerangka etika digital yang mencakup tata kelola data, evaluasi pelayanan, dan pengawasan terhadap komersialisasi. Strategi tersebut diharapkan menjadi kerangka konseptual bagi gereja dalam mengembangkan pelayanan digital yang kontekstual, bertanggung jawab, dan tetap setia pada misi Kristus.